Os significados do consumo e uso nocivo de álcool e de outras drogas pelos alunos de graduação da PUC-SP, Campus Monte Alegre, 2005 2007: uma questão acadêmica desafiadora - Sant'Anna, Silvio Nececkaite (2008)
This thesis deals with the harmful consumption and utilization of alcohol and other drugs at Pontifícia Universidade Católica de São Paulo (PUC-SP), Monte Alegre campus, and proceeds to discuss this matter, as well as the taints over the students involved. The study was carried out at PUC-SP, university responsible for the academic formation of 13,581 students in the school year 2007. Among them, 1,115 students from eight (8) colleges and twenty-two (22) graduation courses were significant subjects of the survey, and the quantitative methodology was applied. The overall purpose was to acknowledge and review the current reality of PUCSP s graduation course students, with respect to empirical evidence of harmful consumption and utilization of alcohol and other drugs, or even chemical dependency at the Monte Alegre campus. It has proposed to deepen the discussion concerning this issue aiming at finding other ways appointing to a more comprehensive and effective policy of approaching, bio-psycho-social and educational assistance to those involved. The central theme rests on the existing paradox between PUC-SP s academic educational proposal and the familiarity with the harmful consumption and utilization of alcohol and other drugs by its students, referenced in the bio-psycho-social and contemporaneous literature from Brazilian and foreign authors. Such study disclosed that the social stigma that PUC-SP is a marijuana den lacks scientific substantiation, inasmuch as, out of the searched universe, only 6% are lenient to using alcohol and other drugs; 4% feel curious, and 1% has no strong opinion about it. The survey evidenced that at PUC-SP there is a deficiency of proper policies to face the harmful consumption and utilization of alcohol and other drugs, establishing a challenging academic question